The Effect of Decreased Voice Quality in a VoIP Network - Ahmad , Jazya M. (Scientific Journal for Faculty of Science-Sirte University, 2022)
Voice over Internet Protocol (VOIP) is a telephone system telecommunication technology that uses an IP (Internet Protocol) network. VoIP offers numerous advantages for customers and communication, including cost savings, phone and service portability, mobility, and integration with other applications. Because voice is sensitive to delay and jitter, bandwidth must be guaranteed while it is being transported. There are some issues with Quality of Service (QoS), the most significant of which is latency in VOIP. The purpose of this paper is to investigate the effect of delay on speech quality in Voice Over Internet Protocol (VOIP). One source of delay is the buffer that already exists in the original multiplexing’-multicast node. There will be no buffering to store packets in the proposed multiplexing’-multicast algorithm, so any packet received will be sent immediately unless the packet arrives after a specific time or in a different order, where OPNET IT Guru Academic Edition simulation was used to analyze network performance.